Tract‐specific and age‐related variations of the spinal cord microstructure: a multi‐parametric MRI study using diffusion tensor imaging (DTI) and inhomogeneous magnetization transfer (ihMT). (21st April 2016) - Taso, Manuel; Girard, Olivier M.; Duhamel, Guillaume; Le Troter, Arnaud; Feiweier, Thorsten; Guye, Maxime; Ranjeva, Jean‐Philippe; Callot, Virginie
Abstract : Being able to finely characterize the spinal cord (SC) microstructure and its alterations is a key point when investigating neural damage mechanisms encountered in different central nervous system (CNS) pathologies, such as multiple sclerosis, amyotrophic lateral sclerosis or myelopathy. Based on novel methods, including inhomogeneous magnetization transfer (ihMT) and dedicated SC probabilistic atlas post‐processing, the present study focuses on the in vivo characterization of the healthy SC tissue in terms of regional microstructure differences between (i) upper and lower cervical vertebral levels and (ii) sensory and motor tracts, as well as differences attributed to normal aging. Forty‐eight healthy volunteers aged from 20 to 70 years old were included in the study and scanned at 3 T using axial high‐resolution T 2 *‐w imaging, diffusion tensor imaging (DTI) and ihMT, at two vertebral levels (C2 and C5). A processing pipeline with minimal user intervention, SC segmentation and spatial normalization into a reference space was implemented in order to assess quantitative morphological and structural parameters (cross‐sectional areas, scalar DTI and MT/ihMT metrics) in specific white and gray matter regions of interest. The multi‐parametric MRI metrics collected allowed upper and lower cervical levels to be distinguished, with higher ihMT ratio (ihMTR), higher axial diffusivity ( λ ∥ ) and lower radial diffusivity ( λ ⊥ ) at C2 compared with C5. Significant differences were also observed between white matter fascicles, with higher ihMTR and lower λ ∥ in motor tracts compared with posterior sensory tracts. Finally, aging was found to be associated with significant metric alterations (decreased ihMTR and λ ∥ ). The methodology proposed here, which can be easily transferred to the clinic, provides new insights for SC characterization. It bears great potential to study focal and diffuse SC damage in neurodegenerative and demyelinating diseases. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Diffusion tensor imaging and inhomogeneous magnetization transfer acquisitions were combined with a spinal cord (SC) atlas‐based post‐processing pipeline in order to refine the characterization of the normal SC microstructure. Differences between upper and lower vertebral levels as well as tract‐specific structural differences were emphasized. Age‐related tissue destructuration was also highlighted. This multiparametric approach holds great promise for improving the investigation of the neural damage mechanisms occurring in SC pathologies.